THE FUNCTIONS OF DISCOURSE MARKER LIKE IN THE DEBATE OF THE U.S. PRESIDENTIAL CANDIDATES - Rusdiyanto, Zaiful; Ekawati, Rosyida (Jurusan Sastra Indonesia, 2024)
This study aims to investigate the functions of discourse marker like used by presidential candidates in debate. It is a descriptive qualitative method. The source of data in this study is The First U.S Presidential Debate 2020, while the data are the utterances of both Donald Trump and Joe Biden which contain the use discourse marker like. The results show five out of six functions of discourse marker like found in the debate. They are introducing an explanation, introducing an example, marking an approximate number or quantity, marking lexical focus, discourse linking and restarting. One of the functions which mostly used by presidential candidates is introduction an explanation. However, one out of six functions that is not found in the debate is searching for the appropriate expression.